Transcriptome analysis reveals glycometabolism and antioxidation-related genes involved in the antifungal immune response of Spodoptera frugiperda larvae against Beauveria bassiana infection - Yongkai MAO; Jiequn YI; Yinjie CHENG; Han WU; Jihu LI; Mingjiang LIN; Hanliang XU; Zhenqiang QIN; Jianbai LIU (European Journal of Entomology)
Spodoptera frugiperda damages crops around the world and has developed resistance to many pesticides. Beauveria bassiana, a fungus that is harmless to humans and the environment, is widely used in pest control. In our study, differentially expressed genes between S. frugiperda larvae, both exposed and unexposed, to B. bassiana were analyzed by transcriptome sequencing. More than 160 Gb of clean data were obtained, and 2767 and 2892 DEGs were identified in LH36vsCK36 and LH144vsCK144, respectively. To explore the roles of glycometabolism and antioxidation-related enzyme genes in S. frugiperda against B. bassiana infection, the expression patterns of those genes when under attack from B. bassiana were analyzed by quantitative real-time PCR. The results of enzyme activity experiments revealed that S. frugiperda larvae exposed to B. bassiana could upregulate these genes to produce more enzymes related to the maintainance of normal glucose metabolism, as well as regulate the expression of detoxification and antioxidant factors to enhance the larvae's detoxification and antioxidant capacity. The result implied that glycometabolism and antioxidation-related enzymes and genes played critical roles in the antifungal immune process of S. frugiperda larvae. This study enhances our understanding of the molecular mechanisms related to regulation of metabolism and provides a basis for exploring new methods to combat antifungal resistance in S. frugiperda.